Preparation method and application of lithium ion battery glass anode material
The waste graphite is regenerated through ultra-fast flash joule heating technology and combined with ZIF-62 glass, which solves the problem of insufficient stability and conductivity of the anode material of lithium-ion battery during circulation, achieving efficient electrochemical performance improvement and high-value utilization of graphite.
Patent Information
- Application Number
- CN202411692232.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-25
- Publication Date
- 2025-02-28
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing lithium-ion battery anode materials, especially metal organic frame materials, have problems such as degradation of stability and poor electronic conductivity during the battery cycle, resulting in insufficient energy storage capacity and cycle stability.
Ultra-fast flash joule heating technology is used to regenerate waste graphite and combine it with ZIF-62 glass to prepare glass ZIF-62 material through melt quenching technology to improve its electronic conductivity and structural stability.
The electrochemical performance of ZIF-62 glass is improved, the cycle stability and energy storage capacity of the electrode are enhanced, the preparation cost and time are reduced, and the high-value utilization of graphite is achieved.
Smart Images

Figure CN119542418A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of new energy material recycling and regeneration, and in particular to a preparation method and application of a lithium ion battery glass anode material. Background Art
[0002] Graphite has become one of the most commonly used anode materials in lithium-ion batteries due to its excellent electrical conductivity and chemical stability. Although the cost of battery-grade graphite is quite high, the recycling of waste graphite is often overlooked. In recent years, the recycling technology of graphite has made significant progress, including methods such as high-temperature thermal treatment and chemical treatment. However, these methods usually involve complex process flows and may bring potential environmental risks. Therefore, it has become particularly urgent to improve the high energy consumption and environmental impact of the graphite recycling process.
[0003] Metal-organic framework materials have shown great potential in the field of energy storage due to their unique structural and functional properties, such as high porosity, diverse chemical functionality, and adjustable pore size. As anode materials for lithium-ion batteries, this material has a high specific surface area and abundant active sites, and is expected to provide excellent energy storage capacity. However, metal-organic framework materials face two major challenges as anode materials for lithium-ion batteries: first, the destruction of the material skeleton during battery cycling may lead to a decrease in its stability; second, metal-organic framework materials exhibit poor electronic conductivity in electrochemical applications.
[0004] As a subclass of metal-organic framework materials, certain zeolitic imidazolate framework materials (ZIFs) can be melted at high temperatures and transformed into a glassy state through a melt-quenching process, namely melt-quenched metal-organic framework glass. This type of new glass material not only has unique structural and chemical properties, but also exhibits excellent thermal, mechanical and dynamic properties. In particular, ZIF-62 glass, with the chemical formula Co[Im1.75bIm0.25], shows the strongest glass-forming ability among all known metal-organic framework glasses. As a disordered material, the unique melt-quenching process of ZIF-62 glass gives it an amorphous structure, thus exhibiting excellent mechanical and thermal properties, as well as small volume changes. These characteristics make ZIF-62 glass potentially an excellent electrode material, which is expected to improve Li + transport kinetics and enhance the cycling stability of the electrode.
[0005] However, based on the current research on ZIF-62 glass materials as electrode materials for lithium-ion batteries, ZIF-62 glass materials still face many challenges, including poor electronic conductivity, weak structural stability and low reversible capacity. Summary of the invention
[0006] In view of the above problems existing in the prior art, the present invention provides a preparation method and application of a lithium-ion battery glass anode material. The glass anode synthesis strategy provided by the present invention not only meets the requirements of environmental sustainability, but also effectively improves the electrochemical performance of ZIF-62 glass and maximizes the regeneration potential of graphite in waste anode materials; the present invention will contribute to the high-value utilization of graphite, and will also provide a new perspective for the development of low-cost, high-performance, sustainable battery technology.
[0007] The technical solution of the present invention is as follows:
[0008] A method for preparing a lithium ion battery glass anode material, the method comprising the following steps:
[0009] (1) Grind the anode waste containing graphite and load it into a quartz reactor with a loading mass of 90-110 mg / cm 2 , the resistance is 1-5Ω; then, a voltage of 160-190V is applied to both ends of the reactor for flash Joule heating, and a pulse current is applied to the reactor to achieve direct regeneration of graphite in the anode waste; after the reaction is completed and cooled to room temperature, the flash anode waste can be obtained; the flash anode waste can be acid-leached and dried to obtain flash regenerated graphite;
[0010] (2) Weigh imidazole and benzimidazole and dissolve them in N,N-dimethylformamide (DMF), then dissolve Co(NO3)2·6H2O in the above solution and stir evenly; place the mixed solution in a polytetrafluoroethylene liner for improved solvent thermal pretreatment, react at 120-150°C for 24-72h, and obtain ZIF-62 crystals after centrifugal drying; calcine the finely ground ZIF-62 crystals at high temperature, and obtain ZIF-62 glass after natural cooling;
[0011] (3) mixing the flash regenerated graphite obtained in step (1) with carbon black to prepare a composite conductive agent;
[0012] (4) The composite conductive agent prepared in step (3) is mixed with the ZIF-62 glass prepared in step (2) and a binder to obtain the lithium ion battery glass anode material.
[0013] Preferably, in step (1), the anode waste is ground to pass through a 200-300 mesh sieve.
[0014] Preferably, the time for applying the pulse current to the reactor in step (1) is 300-700 ms.
[0015] Preferably, the acid leaching in step (1) uses 0.1-0.5 mol·L -1 of dilute HCl, the acid leaching time is 20-60min.
[0016] More preferably, the acid leaching process in step (1) uses 0.1 mol·L -1 Dilute HCl is best.
[0017] More preferably, the loading mass in the preparation process of step (1) is 100 mg / cm 2 For the best.
[0018] More preferably, the optimal resistance of the sample in step (1) is 3Ω.
[0019] More preferably, the reaction in step (1) is best performed at a voltage of 180V.
[0020] Furthermore, in the preparation process described in step (1), the diameter of the quartz reactor is selected to be 6-10 mm.
[0021] Furthermore, the discharge time in the flash Joule heating process of step (1) is controlled by a programmable millisecond-level Arduino relay with a delay function.
[0022] Furthermore, the drying condition in step (1) is drying at a temperature of 100-120° C. for 12-24 hours.
[0023] Preferably, the mass ratio of imidazole, benzimidazole and Co(NO3)2·6H2O in step (2) is 1-5:1:3-7, and 23-30 mL of N,N-dimethylformamide is required for every 196 mg of imidazole.
[0024] Preferably, the drying condition in step (2) is drying under vacuum conditions at 100-120° C. for 12-36 hours.
[0025] Preferably, the high temperature calcination in step (2) is carried out at a temperature of 5-15°C·min -1 The temperature is raised to 440-480°C at a rate of 10000 ℃ and kept at this temperature for 2.5-7.5 minutes. The entire high-temperature calcination process is carried out in an argon atmosphere.
[0026] More preferably, the stirring time in step (2) is 0.5-1.5 h, with 1 h being optimal.
[0027] More preferably, the reaction temperature of step (2) is optimally 130°C.
[0028] More preferably, the optimal reaction time of step (2) is 60 h.
[0029] Preferably, the mass ratio of the flash regenerated graphite to carbon black in step (3) is 1-3:1-7.
[0030] More preferably, the optimal ratio of regenerated graphite and carbon black in step (3) is 1:3.
[0031] Preferably, in step (4), the mass ratio of the ZIF-62 glass, the composite conductive agent and the binder is 6-8:1-3:0.8-1.
[0032] More preferably, in step (4), the mass ratio of the ZIF-62 glass, the mass of the composite conductive agent and the mass of the binder is 7:2:1, which is the best.
[0033] The present invention also provides an application of a lithium ion battery glass anode material prepared by the method, wherein the anode material is used to make a lithium ion half-cell, and during preparation, the anode material is coated on a copper foil current collector, with a loading of 0.8-1.2 mg / cm 2 .
[0034] More preferably, when assembled into a CR2032 button cell, the anode material loading is 1.0 mg / cm 2 For the best.
[0035] Furthermore, the binder is polyvinylidene fluoride (PVDF), and N-methyl-2-pyrrolidone (NMP) is used as a solvent in a mass ratio of PVDF:NMP=0.8-1:5-10, and stirred for 10-30 minutes to ensure the formation of a uniform slurry.
[0036] The beneficial technical effects of the present invention are:
[0037] 1. The ultrafast flash Joule heating technology used in the present invention provides an innovative solution for graphite recycling with its high efficiency and environmentally friendly characteristics. This technology can regenerate waste graphite in just a few seconds, repair its crystal defects and restore its conductivity, which not only helps to increase the value of graphite, but also provides a new perspective for the development of low-cost, high-performance and sustainable battery technology.
[0038] 2. The present invention can recover precious metal resources from the treated waste by using dilute acid, which is expected to reduce the impact of toxic heavy metals on the environment.
[0039] 3. The glassy ZIF prepared by the melt quenching technology of the present invention shows higher mechanical strength, can reduce the pulverization of the material during the cycle, and maintain the structural integrity of the electrode material. Compared with the prior art, the cooling process of the melt quenching technology adopted by the present invention is natural cooling with the furnace rather than rapid supercooling, which not only improves the safety of the process, but also effectively reduces the difficulty of the process.
[0040] 4. In the process of preparing ZIF-62 glass, the present invention uses only cobalt nitrate as the metal salt raw material, rather than zinc nitrate or two mixed metal salts as the metal source. Cobalt nitrate has high stability and predictability during the synthesis process, and cobalt nitrate has good solubility in dimethylformamide (DMF) solvent, can efficiently participate in the coordination reaction with organic ligands, and effectively improve the reaction efficiency. These advantages jointly ensure the efficiency and quality of ZIF-62 synthesis.
[0041] 5. Compared with the prior art, the present invention combines ultrafast flash Joule heating technology with ZIF-62 glass, which not only improves the electronic conductivity of ZIF glass, but also fully taps the electrochemical potential of waste graphite. At the same time, this efficient combination strategy not only greatly saves preparation cost and time, but also effectively makes up for the intrinsic defect of poor electronic conductivity of ZIF-62 glass material.
[0042] 6. In terms of the raw material ratio and process parameters when preparing the anode material, the present invention finally determines the optimal parameters through verification of the examples and comparative examples. For example, the anode material prepared by the composite conductive agent containing 25% flash regenerated graphite has a good conductivity at 1A·g -1 After 1000 charge and discharge cycles at a current density of 1.5 %, the discharge capacity increased fourfold to 407.3 mAh g -1 This advantage is due to the unique open network structure and rich pore properties of ZIF-62 glass, which makes its volume change very small during electrochemical cycling, thus significantly enhancing the performance stability.
[0043] 7. The present invention not only provides an effective technical path for the resource recovery and reuse of waste lithium-ion batteries, but also lays a solid theoretical foundation for the development of environmentally friendly battery recycling technology. BRIEF DESCRIPTION OF THE DRAWINGS
[0044] Figure 1 The XRD pattern of the glass anode electrode sheet prepared in Example 1;
[0045] Figure 2 This is a capacity performance diagram of the glass anode material prepared in Example 1;
[0046] Figure 3 The XRD pattern of the glass anode electrode sheet prepared in Example 2;
[0047] Figure 4 This is a capacity performance diagram of the glass anode material prepared in Example 2;
[0048] Figure 5 This is the TEM image of the glass anode prepared in Example 2 after 1000 cycles;
[0049] Figure 6The XRD pattern of the glass anode electrode sheet prepared in Example 3;
[0050] Figure 7 This is a capacity performance diagram of the glass anode material prepared in Example 3;
[0051] Figure 8 The XRD pattern of the glass anode electrode sheet prepared in Example 4;
[0052] Fig. 9 This is a capacity performance diagram of the glass anode material prepared in Example 4;
[0053] Fig.10 The XRD pattern of the glass anode electrode sheet prepared in Example 5;
[0054] Fig.11 This is a capacity performance diagram of the glass anode material prepared in Example 5;
[0055] Fig.12 The XRD pattern of the glass anode electrode sheet prepared in Comparative Example 1;
[0056] Fig.13 This is a capacity performance diagram of the glass anode material prepared in Comparative Example 1;
[0057] Fig.14 TEM image of the glass anode prepared in Comparative Example 1 after 1000 cycles; DETAILED DESCRIPTION
[0058] The present invention is described in detail below in conjunction with the accompanying drawings and embodiments. Obviously, the described embodiments are only a part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0059] Embodiment 1:
[0060] 1. This embodiment provides a preparation method and application of a lithium-ion battery glass anode:
[0061] (1) Grind the anode waste containing graphite to pass through a 200-mesh sieve and place it in a quartz reaction tube with a diameter of 6 mm, where the loading mass is 90 mg / cm 2 , adjusting the resistance of the sample to 1Ω. The discharge time during the flash Joule heating process was controlled by a programmable millisecond Arduino relay with a delay function. The reaction was carried out at a voltage of 160V, and a pulse current was applied to the reactor to achieve direct regeneration of waste graphite. The optimized pulse duration was 300ms. After the reaction was completed and the equipment was cooled to room temperature, the reactor was disassembled to obtain the flash anode waste. Subsequently, 0.1mol·L-1 The small amount of precious metal (Li) contained in the waste is leached out by dilute HCl. After leaching for 60 minutes, the anode waste is placed in an oven at 100°C and dried for 12 hours to obtain flash regenerated graphite.
[0062] (2) Weigh the raw materials according to the mass ratio of imidazole: benzimidazole: Co(NO3)2·6H2O = 5:1:7 and dissolve them in N,N-dimethylformamide (DMF). 23 mL of DMF is required for every 196 mg of imidazole. Stir for 0.5 h. Pour the mixed solution into a polytetrafluoroethylene liner, ensuring that the filling amount does not exceed 80% of the internal volume of the container. Perform improved solvent thermal pretreatment and react at 120°C for 24 h. After the reaction is completed, cool the reactor to room temperature, separate the purple product from the solution by centrifugation, and dry it at 100°C under vacuum for 12 h to obtain ZIF-62 crystals. Finely grind the ZIF-62 crystals that can pass through a 200-mesh sieve at 5°C·min -1 The ZIF-62 glass was obtained by heating the glass to 440°C at a heating rate of 1.50 °C and calcining it at this temperature for 2.5 min and then cooling it naturally to room temperature. The entire calcination process was carried out in an argon atmosphere.
[0063] (3) The flash regenerated graphite and carbon black of step (1) are mixed in a mass ratio of 1:4 to prepare a composite conductive agent.
[0064] Second, this embodiment also provides a method for using the above-mentioned material to make a lithium-ion battery anode electrode, and the specific steps are as follows:
[0065] ZIF-62 glass, composite conductive agent, PVDF and N-methyl-2-pyrrolidone (NMP) solvent were weighed in a mass ratio of 6:3:1:5 and stirred for 10 minutes to ensure the formation of a uniform slurry with appropriate viscosity. The obtained active material was uniformly loaded onto the vacuum-dried copper foil current collector, with a loading of about 0.8 mg / cm 2 , a lithium-ion battery glass anode electrode sheet mixed with a composite conductive agent and ZIF-62 glass can be obtained.
[0066] A CR2032 button-type lithium-ion half-cell was assembled with an electrode sheet loaded with active materials as the working electrode, a metal lithium sheet as the counter electrode, and a lithium salt solution as the electrolyte for electrochemical characterization.
[0067] The XRD characterization of the material obtained in Example 1 is as follows Figure 1 As shown, the capacity performance is Figure 2 shown.
[0068] Embodiment 2:
[0069] 1. This embodiment provides a preparation method and application of a lithium-ion battery glass anode:
[0070] (1) Grind the anode waste containing graphite to pass through a 200-mesh sieve and place it in a quartz reaction tube with a diameter of 8 mm, where the loading mass is 100 mg / cm 2 , adjusting the resistance of the sample to 3Ω. The discharge time during the flash Joule heating process was controlled by a programmable millisecond Arduino relay with a delay function. The reaction was carried out at a voltage of 180V, and a pulse current was applied to the reactor to achieve direct regeneration of waste graphite. The optimized pulse duration was 500ms. After the reaction was completed and the equipment was cooled to room temperature, the reactor was disassembled to obtain the flash anode waste. Subsequently, 0.1mol·L -1 The dilute HCl is used to leach a small amount of precious metal (Li) from the waste. After acid leaching for 50 minutes, the anode waste is placed in an oven at 110°C and dried for 16 hours to obtain flash regenerated graphite.
[0071] (2) Weigh the raw materials according to the mass ratio of imidazole: benzimidazole: Co(NO3)2·6H2O = 4:1:6 and dissolve them in N,N-dimethylformamide (DMF). 23 mL of DMF is required for every 196 mg of imidazole. Stir for 1 hour. Pour the mixed solution into a polytetrafluoroethylene liner to ensure that the filling amount does not exceed 80% of the internal volume of the container. Perform improved solvent thermal pretreatment and react at 130°C for 60 hours. After the reaction is completed, cool the reactor to room temperature, separate the purple product from the solution by centrifugation, and dry it at 110°C under vacuum for 24 hours to obtain ZIF-62 crystals. Finely grind the ZIF-62 crystals that can pass through a 200-mesh sieve at 10°C·min -1 The ZIF-62 glass was obtained by heating the sample to 460°C at a heating rate of 100°C and calcining it for 5 minutes at this temperature and then cooling it to room temperature naturally. The whole calcination process was carried out in an argon atmosphere.
[0072] (3) The flash regenerated graphite and carbon black of step (1) are mixed in a mass ratio of 1:3 to prepare a composite conductive agent.
[0073] Second, this embodiment also provides a method for using the above-mentioned material to make a lithium-ion battery anode electrode, and the specific steps are as follows:
[0074] ZIF-62 glass, composite conductive agent, PVDF and N-methyl-2-pyrrolidone (NMP) solvent were weighed in a mass ratio of 7:2:1:6 and stirred for 20 minutes to ensure the formation of a uniform slurry with appropriate viscosity. The obtained active material was uniformly loaded onto the vacuum-dried copper foil current collector, with a loading of about 1 mg / cm 2 , a lithium-ion battery glass anode electrode sheet mixed with a composite conductive agent and ZIF-62 glass can be obtained.
[0075] A CR2032 button-type lithium-ion half-cell was assembled with an electrode sheet loaded with active materials as the working electrode, a metal lithium sheet as the counter electrode, and a lithium salt solution as the electrolyte for electrochemical characterization.
[0076] The XRD characterization of the material obtained in Example 2 is as follows Figure 3 As shown, the capacity performance is Figure 4 As shown in Figure 2, the TEM characterization after 1000 cycles is as follows: Figure 5 shown.
[0077] Embodiment 3:
[0078] 1. This embodiment provides a preparation method and application of a lithium-ion battery glass anode:
[0079] (1) Grind the anode waste containing graphite to pass through a 200-mesh sieve and place it in a quartz reaction tube with a diameter of 10 mm, where the loading mass is 110 mg / cm 2 , adjusting the resistance of the sample to 5Ω. The discharge time during the flash Joule heating process is controlled by a programmable millisecond Arduino relay with a delay function. The reaction is carried out at a voltage of 190V, and a pulse current is applied to the reactor to achieve direct regeneration of waste graphite. The optimized pulse duration is 700ms. After the reaction is completed and the equipment is cooled to room temperature, the reactor is disassembled to obtain the flash anode waste. Subsequently, 0.1mol·L -1 The dilute HCl is used to leach a small amount of precious metal (Li) from the waste. After acid leaching for 40 minutes, the anode waste is placed in a 120°C oven and dried for 18 hours to obtain flash regenerated graphite.
[0080] (2) Weigh the raw materials according to the mass ratio of imidazole: benzimidazole: Co(NO3)2·6H2O = 3:1:5 and dissolve them in N,N-dimethylformamide (DMF). 23 mL of DMF is required for every 196 mg of imidazole. Stir for 1.5 h. Pour the mixed solution into a polytetrafluoroethylene liner, ensuring that the filling amount does not exceed 80% of the internal volume of the container. Perform improved solvent thermal pretreatment and react at 140°C for 72 h. After the reaction is completed, cool the reactor to room temperature, separate the purple product from the solution by centrifugation, and dry it at 120°C under vacuum for 36 h to obtain ZIF-62 crystals. Finely grind the ZIF-62 crystals that can pass through a 200-mesh sieve at 15°C·min -1 The ZIF-62 glass was obtained by heating the glass to 480°C at a heating rate of 100°C and calcining it at this temperature for 7.5 minutes and then cooling it to room temperature naturally. The entire calcination process was carried out in an argon atmosphere.
[0081] (3) The flash regenerated graphite and carbon black of step (1) are mixed in a mass ratio of 3:7 to prepare a composite conductive agent.
[0082] Second, this embodiment also provides a method for using the above-mentioned material to make a lithium-ion battery anode electrode, and the specific steps are as follows:
[0083] ZIF-62 glass, composite conductive agent, PVDF and N-methyl-2-pyrrolidone (NMP) solvent were weighed in a mass ratio of 8:1:1:8 and stirred for 30 minutes to ensure the formation of a uniform slurry with appropriate viscosity. The obtained active material was uniformly loaded onto the vacuum-dried copper foil current collector, with a loading of about 1.2 mg / cm 2 , a lithium-ion battery glass anode electrode sheet mixed with a composite conductive agent and ZIF-62 glass can be obtained.
[0084] A CR2032 button-type lithium-ion half-cell was assembled with an electrode sheet loaded with active materials as the working electrode, a metal lithium sheet as the counter electrode, and a lithium salt solution as the electrolyte for electrochemical characterization.
[0085] The XRD characterization of the material obtained in Example 3 is as follows Figure 6 As shown, the capacity performance is Figure 7 shown.
[0086] Embodiment 4:
[0087] 1. This embodiment provides a preparation method and application of a lithium-ion battery glass anode:
[0088] (1) Grind the anode waste containing graphite to pass through a 220-mesh sieve and load it into a quartz reaction tube with a diameter of 7 mm, where the loading mass is 90 mg / cm 2 , adjusting the resistance of the sample to 2Ω. The discharge time during the flash Joule heating process is controlled by a programmable millisecond Arduino relay with a delay function. The reaction is carried out at a voltage of 170V, and a pulse current is applied to the reactor to achieve direct regeneration of waste graphite. The optimized pulse duration is 400ms. After the reaction is completed and the equipment is cooled to room temperature, the reactor is disassembled to obtain the flash anode waste. Subsequently, 0.2mol·L -1 The dilute HCl is used to leach a small amount of precious metal (Li) from the waste. After acid leaching for 30 minutes, the anode waste is placed in a 100°C oven and dried for 20 hours to obtain flash regenerated graphite.
[0089] (2) Weigh the raw materials according to the mass ratio of imidazole: benzimidazole: Co(NO3)2·6H2O = 2:1:4 and dissolve them in N,N-dimethylformamide (DMF). 26 mL of DMF is required for every 196 mg of imidazole. Stir for 0.5 h. Pour the mixed solution into a polytetrafluoroethylene liner to ensure that the filling amount does not exceed 80% of the internal volume of the container. Perform an improved solvent thermal pretreatment and react at 150°C for 36 h. After the reaction is completed, cool the reactor to room temperature, separate the purple product from the solution by centrifugation, and dry it at 100°C under vacuum for 12 h to obtain ZIF-62 crystals. Finely grind the ZIF-62 crystals that can pass through a 200-mesh sieve at 5°C·min -1 The ZIF-62 glass was obtained by heating the glass to 450°C at a heating rate of 100°C and calcining it at this temperature for 2.5 minutes and then cooling it naturally to room temperature. The entire calcination process was carried out in an argon atmosphere.
[0090] (3) The flash regenerated graphite and carbon black of step (1) are mixed in a mass ratio of 1:1 to prepare a composite conductive agent.
[0091] Second, this embodiment also provides a method for using the above-mentioned material to make a lithium-ion battery anode electrode, and the specific steps are as follows:
[0092] ZIF-62 glass, composite conductive agent, PVDF and N-methyl-2-pyrrolidone (NMP) solvent were weighed in a mass ratio of 6:3:1:5 and stirred for 10 minutes to ensure the formation of a uniform slurry with appropriate viscosity. The obtained active material was uniformly loaded onto the vacuum-dried copper foil current collector, with a loading of about 0.8 mg / cm 2 , a lithium-ion battery glass anode electrode sheet mixed with a composite conductive agent and ZIF-62 glass can be obtained.
[0093] A CR2032 button-type lithium-ion half-cell was assembled with an electrode sheet loaded with active materials as the working electrode, a metal lithium sheet as the counter electrode, and a lithium salt solution as the electrolyte for electrochemical characterization.
[0094] The XRD characterization of the material obtained in Example 4 is as follows Figure 8 As shown, the capacity performance is Fig. 9 shown.
[0095] Embodiment 5:
[0096] 1. This embodiment provides a preparation method and application of a lithium-ion battery glass anode:
[0097] (1) Grind the anode waste containing graphite to pass through a 240-mesh sieve and place it in a quartz reaction tube with a diameter of 9 mm, where the loading mass is 100 mg / cm 2, adjusting the resistance of the sample to 4Ω. The discharge time during the flash Joule heating process is controlled by a programmable millisecond Arduino relay with a delay function. The reaction is carried out at a voltage of 180V, and a pulse current is applied to the reactor to achieve direct regeneration of waste graphite. The optimized pulse duration is 600ms. After the reaction is completed and the equipment is cooled to room temperature, the reactor is disassembled to obtain the flash anode waste. Subsequently, 0.3mol·L -1 The dilute HCl is used to leach a small amount of precious metal (Li) from the waste. After acid leaching for 20 minutes, the anode waste is placed in an oven at 110°C and dried for 22 hours to obtain flash regenerated graphite.
[0098] (2) Weigh the raw materials according to the mass ratio of imidazole: benzimidazole: Co(NO3)2·6H2O = 1:1:3 and dissolve them in N,N-dimethylformamide (DMF). 30 mL of DMF is required for every 196 mg of imidazole. Stir for 1 hour. Pour the mixed solution into a polytetrafluoroethylene liner to ensure that the filling amount does not exceed 80% of the internal volume of the container. Perform improved solvent thermal pretreatment and react at 120°C for 48 hours. After the reaction is completed, cool the reactor to room temperature, separate the purple product from the solution by centrifugation, and dry it at 110°C under vacuum conditions for 24 hours to obtain ZIF-62 crystals. Finely grind the ZIF-62 crystals that can pass through a 200-mesh sieve at 10°C·min -1 The ZIF-62 glass was obtained by heating the glass to 470°C at a heating rate of 100°C and calcining it for 5 minutes at this temperature and then cooling it to room temperature naturally. The entire calcination process was carried out in an argon atmosphere.
[0099] (3) The flash regenerated graphite and carbon black of step (1) are mixed in a mass ratio of 3:1 to prepare a composite conductive agent.
[0100] Second, this embodiment also provides a method for using the above-mentioned material to make a lithium-ion battery anode electrode, and the specific steps are as follows:
[0101] ZIF-62 glass, composite conductive agent, PVDF and N-methyl-2-pyrrolidone (NMP) solvent were weighed in a mass ratio of 7:2:1:6 and stirred for 20 minutes to ensure the formation of a uniform slurry with appropriate viscosity. The obtained active material was uniformly loaded onto the vacuum-dried copper foil current collector, with a loading of about 1 mg / cm 2 , a lithium-ion battery glass anode electrode sheet mixed with a composite conductive agent and ZIF-62 glass can be obtained.
[0102] A CR2032 button-type lithium-ion half-cell was assembled with an electrode sheet loaded with active materials as the working electrode, a metal lithium sheet as the counter electrode, and a lithium salt solution as the electrolyte for electrochemical characterization.
[0103] The XRD characterization of the material obtained in Example 5 is as follows Fig.10 As shown, the capacity performance is Fig.11 shown.
[0104] Comparative Example 1:
[0105] This comparative example is based on Example 2, except that the flash regenerated graphite and carbon black are mixed in a mass ratio of 0:1 to prepare a composite conductive agent.
[0106] The XRD characterization of the material obtained in Comparative Example 1 is as follows Fig.12 As shown, the capacity performance is Fig.13 As shown in Figure 2, the TEM characterization after 1000 cycles is as follows: Fig.14 shown.
[0107] Test example:
[0108] (1) From the XRD patterns of the glass anode materials with different flash regenerated graphite contents obtained in the examples and comparative examples, it can be seen that the samples with different flash regenerated graphite contents all exhibit a typical "mantou peak" in the range of 10-20°. As the flash regenerated graphite content increases, the sample shows a diffraction peak corresponding to the graphite (003) crystal plane at 27.8°, and the peak intensity increases significantly with the increase in the regenerated graphite content, which is sufficient to prove the successful preparation of the composite conductive agent.
[0109] (2) From the TEM images of the lithium ion battery anode materials in Example 2 of the present invention and Comparative Example 1 after 1000 cycles, it can be seen that their morphologies are well maintained. This is mainly due to the open network structure of the glass material and the abundant pores inside the ZIF, which effectively alleviate the volume change during the charge and discharge process. In addition, the unique structure of the ZIF-62 glass greatly suppresses the stress accumulation inside the electrode, thereby improving the structural stability of the electrode during the cycle.
[0110] (3) From the capacity performance diagram of the lithium ion battery anode material obtained in the examples and comparative examples, it can be seen that the glass anode containing 25% recycled graphite composite conductive agent has a high conductivity at 1A·g -1 After 1000 charge and discharge cycles at a current density of 1.5 %, the discharge capacity increased fourfold to 407.3 mAh g -1 This performance advantage is due to the unique open network structure and rich pore properties of ZIF-62 glass, which makes its volume change very small during electrochemical cycling, thus significantly enhancing the performance stability.
[0111] (4) Electrical performance test: When loading the battery, the lithium sheet is used as a counter electrode to form a lithium-ion battery with the glass anode material, and the loaded lithium-ion battery is subjected to an electrochemical performance test;
[0112] Capacity performance test: Under the test temperature of 25℃, the loaded battery is mounted on the LAND battery test system, and the charge and discharge voltage range is set to 0.01-3V vs.Li + / Li, current density 1A·g -1 .
[0113] The test results are as follows:
[0114] Example 1 at 1A·g -1 The discharge capacity is 319.6 mAh g after 1000 cycles at a current density of 1.5 V and a voltage range of 0.01-3 V. -1 .
[0115] Example 2 at 1A·g -1 The discharge capacity is 407.3 mAh g after 1000 cycles at a current density of 1.5 V and a voltage range of 0.01-3 V. -1 .
[0116] Example 3 at 1A·g -1 The discharge capacity is 303.5 mAh / g after 1000 cycles at a current density of 1.5 V and a voltage range of 0.01-3 V.
[0117] Example 4 at 1A·g -1 The discharge capacity is 256.6 mAh g after 1000 cycles at a current density of 1.5 V and a voltage range of 0.01-3 V. -1 .
[0118] Example 5 at 1A·g -1 The discharge capacity is 181.2 mAh g after 1000 cycles at a current density of 1.5 V and a voltage range of 0.01-3 V. -1 .
[0119] Comparative Example 1 at 1A·g -1 The discharge capacity is 6.7 mAh g after 1000 cycles at a current density of 1.5 V and a voltage range of 0.01-3 V. -1 .
[0120] Although the embodiments of the present invention have been disclosed as above, they are not limited to the applications listed in the specification and implementation modes, and can be fully applicable to various fields suitable for the present invention. For those familiar with the art, for those of ordinary skill in the art, various changes, modifications, substitutions and variations can be made to these embodiments without departing from the principle and spirit of the present invention. Therefore, without departing from the general concept defined by the claims and the scope of equivalents, the present invention is not limited to specific details.
Claims
1. A method for preparing a lithium ion battery glass anode material, characterized in that: The method comprises the following steps: (1) Grind the anode waste containing graphite and load it into a quartz reactor with a loading mass of 90-110 mg / cm 2 , the resistance is 1-5Ω; then, a voltage of 160-190V is applied to both ends of the reactor for flash Joule heating, and a pulse current is applied to the reactor to achieve direct regeneration of graphite in the anode waste; after the reaction is completed and cooled to room temperature, the flash anode waste can be obtained; the flash anode waste can be acid-leached and dried to obtain flash regenerated graphite; (2) Weigh imidazole and benzimidazole and dissolve them in N,N-dimethylformamide (DMF), then dissolve Co(NO3)2·6H2O in the above solution and stir evenly; place the mixed solution in a polytetrafluoroethylene liner for improved solvent thermal pretreatment, react at 120-150°C for 24-72h, and obtain ZIF-62 crystals after centrifugal drying; calcine the finely ground ZIF-62 crystals at high temperature, and obtain ZIF-62 glass after natural cooling; (3) mixing the flash regenerated graphite obtained in step (1) with carbon black to prepare a composite conductive agent; (4) The composite conductive agent prepared in step (3) is mixed with the ZIF-62 glass prepared in step (2) and a binder to obtain the lithium ion battery glass anode material.
2. The method according to claim 1, characterized in that Step (1) Grind the anode waste until it passes through a 200-300 mesh sieve.
3. The method according to claim 1, characterized in that The time for applying pulse current to the reactor in step (1) is 300-700ms.
4. The method according to claim 1, characterized in that The acid leaching in step (1) uses 0.1-0.5 mol·L -1 of dilute HCl, the acid leaching time is 20-60min.
5. The method according to claim 1, characterized in that The mass ratio of imidazole, benzimidazole and Co(NO3)2·6H2O in step (2) is 1-5:1:3-7, and 23-30 mL of N,N-dimethylformamide is required for every 196 mg of imidazole.
6. The method according to claim 1, characterized in that The drying conditions in step (2) are drying under vacuum conditions at 100-120° C. for 12-36 hours.
7. The method according to claim 1, characterized in that The high temperature calcination in step (2) is carried out at a temperature of 5-15°C·min -1 The temperature is raised to 440-480°C at a rate of 10000 ℃ and kept at this temperature for 2.5-7.5 minutes. The entire high-temperature calcination process is carried out in an argon atmosphere.
8. The method according to claim 1, characterized in that The mass ratio of the flash regenerated graphite to the carbon black in step (3) is 1-3:1-7.
9. The method according to claim 1, characterized in that: In step (4), the mass ratio of the ZIF-62 glass, the composite conductive agent and the adhesive is 6-8:1-3:0.8-1.
10. Application of the lithium ion battery glass anode material prepared by the method according to any one of claims 1 to 9, characterized in that: The anode material is used to make a lithium ion half-battery. During preparation, the anode material is coated on a copper foil current collector with a loading of 0.8-1.2 mg / cm 2 .
Citation Information
Patent Citations
Flash recirculation of batteries
CN117015880A
Metal organic framework glass-based material as well as preparation method and application thereof
CN118231667A
Method for synthesizing expanded graphite from graphite negative electrode of waste lithium battery and application of expanded graphite
CN118790989A
Manufacturing method of artificial graphite powder and artificial graphite fine powder
JP2008050245A